68.4k views
1 vote
Help me out, so I can confirm my answers...:)​

Help me out, so I can confirm my answers...:)​-example-1
User Shew
by
4.8k points

2 Answers

2 votes

Explanation:

18-2b=5a

we want to make 5a the subject so first we 5a to the left so our new equation is 5a+18-2b=0

then we move the 2b infront of the +18 so then our new equation is 5a+2b+18=0 then. we move the +18 to the other side to give 5a+2b=18

User Morgan Koh
by
4.3k points
6 votes

Answer:

Explanation:

i) 18 - 2b = 5a

18 - 2b - 5a = 0

-2b -5a = -18

2b + 5a = 18

5a + 2b = 18

ii) 3a = 5b + 17

3a - 5b = 17

At this time x = 3, y = -5, c= 17

ax + by = c is equivelant to 3a -5b = 17

So another equation is:

3a - 5b = 17

Answer from Gauthmath

User Brietsparks
by
5.3k points